Phacoemulsification Versus Phacotrabeculectomy in Primary Angle-closure Glaucoma with Cataract: Long-Term Clinical Outcomes - Linda Hansapinyo (2020)
Copyright © 2019 Wolters Kluwer Health, Inc. All rights reserved. Precis:Phacotrabeculectomy was more effective in reducing intraocular pressure (IOP) and glaucoma drugs than phacoemulsification alone in primary angle-closure glaucoma (PACG) eyes with cataract but was associated with more postoperative complications, up to 5 years after surgery.Purpose:The purpose of this study was to compare long-term clinical outcomes of phacoemulsification versus phacotrabeculectomy in PACG eyes with cataract.Patients and Methods:The 2 initial prospective randomized controlled trials recruited PACG eyes with cataract using the same criteria and randomized these eyes to receiving either phacoemulsification or phacotrabeculectomy. Clinical data up to 5 years of follow-up were pooled for retrospective analysis.Results:Clinical data of 35 patients in the phacoemulsification group and 44 patients in the phacotrabeculectomy group were analyzed. At 5 years after surgery, the mean IOP was decreased by 20.7% and 29.5% from before surgery to 5 years after phacoemulsification and phacotrabeculectomy, respectively (P<0.001 for both groups). Phacotrabeculectomy was significantly more effective than phacoemulsification in reducing IOP up to 5 years after surgery (P<0.001). At 5 years, the mean number of glaucoma drugs required±1 SD was 1.6±1.2 in the phacoemulsification group, and 0.7±1.0 in the phacotrabeculectomy group (P=0.004). Phacotrabeculectomy was associated with more postoperative complications than phacoemulsification up to 5 years (25 complications in the phacotrabeculectomy group versus 6 in the phacoemulsification group, P<0.001).Conclusions:Phacoemulsification alone reduces IOP and the need for glaucoma drugs in PACG eyes with cataracts for up to 5 years. Phacotrabeculectomy was more effective in reducing IOP and glaucoma drugs than phacoemulsification alone but was associated with more postoperative complications, up to 5 years after surgery.